Production of phenolic compounds from durian peel waste using sub-critical water - Shitu, Abubakar; Muhammad, Aliyu Idris; Yoshida, Hiroyuki; Siajam, Shamsul Izhar (Faculty of Engineering, Universiti Putra Malaysia, 2016)
Due to the little or no commercial value, durian residues are disposed in open spaces and/or in municipal waste stream causing environmental pollution in Malaysia. Durian peel waste (DPW) which accounts for about 65-70% of the whole fruits contained value addition substances such as phenolic compounds (PC). To determine the optimum temperature and time for recovery of PC from DPW, Sub-critical water (SCW) extraction was carried out under reaction temperature (100-360°C at 4 min fixed time) and time (1-30 min and 240°C fixed temperature). After reaction, two main phases were isolated, residual solid and water soluble phases. The aqueous phase was analyzed for PC and total organic carbon (TOC) contents. The results revealed that the maximum PC yield using SCW was 34.600 mg GAE (Gallic acid equivalent)/g at 240°C, 25 min. Moreover, from the results of TOC it shows that with increasing temperature, the TOC yield increase, this indicated that the process proved to be a good technique for conversion of biological waste into value addition materials such as phenolic compounds.